Key Issues for the Sustainable Development of Smallholder Agriculture in the East African Highlands - Pender, John L.; Place, Frank; Ehui, Simeon (International Food Policy Research Institute, 2006)
This book includes a series of studies of income strategies, land use, and agricultural dynamics and their impacts on welfare and natural resources in the highlands of Ethiopia, Kenya, and Uganda. There are several reasons for focusing on the highlands. First, the complex problems of severe poverty, low productivity, and poor natural resource management seem to be the rule rather than the exception. This is critical because the highlands support the majority of rural populations in the region. Second, within the highlands are some of the most densely populated areas in all of Africa. Thus, what happens in the highlands may provide pertinent insights for what is likely to happen as population density increases and agriculture intensifies in the rest of Africa in the future. Third, the highlands also contain a wide variety of agroclimatic conditions, from the semiarid Tigray landscape to the lush humid highlands of Mt. Kenya, and vastly different market opportunities. The varying population density, agricultural potential, and market access conditions are representative of the variation found elsewhere in Africa. And finally, within the highlands are not only many areas beset by problems of poverty and low productivity but some real successes where farmers invest in agriculture and improved resource management and generate significant profits. Therefore, it is possible to understand how different conditions tend to lead to different evolution or intensification processes as well as which factors have been most critical in enabling some communities and farmers to prosper.